Health literacy levels and affecting factors among adults in Northeast Anatolia: Health literacy levels of adults - Kavuncuoğlu, Duygu; Koşan, Zahide; Yılmaz, Sinan; Vançelik, Serhat (Journal of Surgery and Medicine, 2023)
Background/Aim: Health literacy is individuals’ wishes and capacities to develop their own opinions and make decisions regarding health services, their ability to maintain and promote their health, access health-related information, and interpret those messages and information correctly. Although health literacy began being discussed in the 1980s, its importance has become more apparent in recent years. However, greater research with regional and local data is still needed in this field. The purpose of this study was to determine levels of health literacy among adults in central districts of the Erzurum province, Turkey, and to examine the factors affecting these. Methods: This cross-sectional study was performed with 864 individuals from the 15–65 age group living in Erzurum. The questionnaire employed in the research consisted of two parts: a personal information form and the Turkish Health Literacy Scale-32. The questionnaire was applied following receipt of participant consent. SPSS v 24 was used to enter and analyze the data. Descriptive statistics were expressed as percentage, mean, standard deviation, minimum, and maximum values. The chi-square test, Spearman’s correlation analysis, and regression analysis were applied. Statistical significance was set at P<0.05. Results: The mean age of the participants was 35.6 (13.0) years, and 55.8% were women. Additionally, 23.6% (n=204) of participants were educated to a primary school level or were uneducated, and 56.0% were not working in income-generating employment. Health literacy levels were inadequate in 24.1% of participants, problematic in 31.6%, adequate in 27.7%, and perfect in 16.6%. Health literacy levels varied significantly depending on participants’ age groups (P<0.001), sex (P=0.007), education levels (P<0.001), possession of health insurance (P<0.001), presence of chronic disease in themselves or first-degree relatives (P=0.002 and P<0.001, respectively), and history of hospitalization exceeding 15 days (P=0.026). Conclusion: The incidence of inadequate/problematic health literacy was 55.7%. Although it is not an expected rate for health literacy, this rate shows that only half of the population has a sufficient level and a significant inadequacy in health literacy. This shows that insufficient health literacy is widespread in Erzurum and that interventions aimed at health literacy are required in the province as in the country as a whole. Understanding the factors affecting health literacy is important in terms of improving health, health services planning, and intervention in these spheres.